Blurred face recognition using CNN - Kabyar, Myet Wun (Nanyang Technological University, 2024)
Facial recognition systems play a crucial role in numerous applications ranging from security to healthcare purposes. Regardless, these systems face challenges when the images provided are from video sources or of low-quality. In this project, we explore ResNet18, a type of CNN model on KDEF dataset to address the issue of blurred face recognition, focusing on a blur filter with Gaussian Blur.